Pengaruh Harga Produk, Kualitas Produk, Gaya Hidup Terhadap Minat Beli Ulang (Body Scrub Scarlett Di Aplikasi Shopee) - Ardhianti, Dian; Kusuma, Pradana Jati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The economic, cultural, and technological developments impact lifestyles, particularly in the fashion and beauty sectors, leading to significant changes in Indonesia's beauty product market. This study aims to identify factors influencing the repurchase intention of Generation Z consumers for Scarlett body scrub products on the Shopee application. The population and sample selection targeted Generation Z consumers in Semarang, with an unknown number, within the age criteria of 17–30 years. The researcher applied criteria within the Generation Z category with an age range of 13–33 years, as specified. The sample size taken was Sample = (number of indicators x 8) = 14 x 8 = 112 due to the unknown population size. The research method used was quantitative, applying multiple linear regression analysis to test hypotheses. The results of statistical analysis indicate that the product price, product quality, and lifestyle variables have a positive and significant impact on repurchase intention. This study provides valuable insights for companies in designing effective beauty product marketing strategies, focusing on price and understanding consumer lifestyles. The conclusions drawn from this research can serve as a basis for formulating better marketing strategies to enhance consumer repurchase intention in the Indonesian beauty industry. Keywords: product price; product quality; lifestyle; repurchase intention.